Geopolitics of religion: how does religion influence international relations and states’ foreign policies? - Kadri, Hichem; Abdel Salam, El Fatih Abdullahi (Academic Research Publishing Group, 2020)
Undoubtedly, religion is one of the main factors that increasingly contribute to the shaping of international relations. As it was in the European middle ages, religion and geopolitics have always had ties of one sort or another. Imperialism and nationalist doctrines have found purpose and justification in religious differences and, religious zealotry was functioned to be both cause and consequence of the concentration of state power and the rivalries among existing competitors. The involvement of numerous religious groups and movements in the political scene led the situation to be extremely complicated. The purpose of this article is to see to what extent religion as a soft power has a role in forming international politics. Also, to discuss the role the superpowers and regional powers play in dealing with the question of religious issues. With an argument that these issues including religious conflicts are led by international and regional powers which function these groups in a proxy war to be part of their rivalry overpower, and to achieve their national interests through their foreign policies at the cost of considerable environmental degradation and a massive death toll of people.